Penerapan Metode Total Physical Respons (TPR) Melalui Kegiatan Gerak Lagu Dalam Meningkatkan Kemampuan Motorik Anak Usia Dini Kelompok A Di Raudhatul Athfal (RA) Ma’arif Al-Ikhlas - Jubaedah, Endah; nurfadilah, Syifa (LP2M STAI Al-Musaddadiyah Garut, 2022)
Based on initial observations and interviews, several problems were found that affect the inhibition of motor development, including the application of less varied methods, less than optimal stimulus, and the activities provided by the teacher make the child's response less and learning becomes boring, so the use of the right methods, strategies, and approaches are neccesary. One of them by using Total Physical Respons (TPR) is a method created to increase the ability of child's language, but in addition to ncreases the skill of child's motor because this method consists of three elements there are speech, command, motion. To maximize the stimulus given to the application of this Total Physical Response method (TPR) combined with the action of the song, is a singing activity accompanied by a movement. The purpose of this study was tresearch is to determine the motor skills of early childhood group A at RA Ma'arif Al-Ikhlas by applying the Total Physical Response (TPR) method through song movement activities. The types of research is using class action research (PTK) kemmis and tagart design. By using method constructive qualitative and descriptive quantitative. observation,interview,and documentation is made for data collection techniques. The subjects in this study were children's motor development with the object of 13 children consisting of 4 girls and 9 boys. The results of the research conducted showed an increase in children's motor skills, from the results of initial observations of 31% category of children developed as expected and developed very well into 36% later 58 % of the cycle 1. in the cycle 2 increased very quickly from 65% then 77% then 88% at 3rd meeting. this shows significant application of the total physical response (TPR) method through the song gesture activities in improving children's motor skill